The Assets Transfer of A Limited Liability Company by A Director That Has Not Been Authorized in The Articles of Association - Nur Fitri Melnia; Endeh Suhartini (JURNAL ILMIAH LIVING LAW, 2025)
Decision Number 98/Pdt.G/2022/PN.Bgr validates an underhanded sale agreement between GS and JS for LTD SIS assets. Crucially, LTD SIS assets were uncertified at the agreement's time, JS lacked official director approval, and no Ministry of Law and Human Rights sanction existed. This normative legal study employs qualitative data to address these issues. Transferring company assets by a director without proper corporate approvals (articles of association, Ministry decree) constitutes an ultra vires act. JS's actions in Decision 98/Pdt.G/2022/PN.Bgr are deemed ultra vires, harming LTD SIS by selling assets without authorization and receiving payments personally. Based on Article 97 (1) and (2) of the Indonesian Company Law, JS is personally liable, as directors must manage the company with good faith and full responsibility.